13 High sensitive troponin t levels following elective external direct current cardioversion for atrial fibrillation and atrial flutter. (7th October 2015) - Lobo, R; Cahill, C; Blake, O; Abbas, S; Meany, TB; Hennessy, T; Kiernan, TJ
Abstract : Introduction: External transthoracic direct current (DC) cardioversion is a commonly used method of terminating arrhythmias, emergently or electively. It is known that external DC cardioversion can result in a rise in creatine kinase (CK). Previous research has shown that DC cardioversion resulted in subtle myocardial injury as evidenced by CK-MB, troponin I and troponin T increase, even though only minimally. These studies were based on the outdated monophasic defibrillators and older troponin assays. Since early 2010, the new high sensitive troponin T (Hs-trop T) assays have been used to diagnose myocardial injury and have been found to be highly sensitive and specific. This study aimed to assess the effect of external transthoracic DC cardioversion on myocardial injury as measured by the change in Hs-trop T using the more modern biphasic defibrillators in an elective setting. Methods: Patients who were admitted for a day-case elective DC cardioversion for atrial fibrillation or atrial flutter were asked to participate in the study. DC cardioversion was performed using the Phillips Heartstart XL biphasic defibrillator. For cardioversions that failed at 200 Joules, the Physio-Control Lifepak 20e 360 J biphasic defibrillator was used. Hs-trop T levels were taken pre-cardioversion and at 6 h post-cardioversion (in keeping with the Third Universal Definition of Myocardial Infarction guidelines on biomarker detection of myocardial injury with necrosis). The assay used was the Roche Elecsys Troponin T hs (high sensitive) immunoassay. Quantitative analysis for haemolysis, icterus and lipaemia (which could result in interference with the Hs-trop T assay) were measured in each blood sample that was taken using the Abbott Architect c16000. Results: A total of 120 cardioversions were done on 101 patients. Analysis of each of the blood sample taken showed no raised haemolytic, icteric or lipaemic indices above the recommendations for the Hs-trop T assay. Median number of shocks was 1, and the maximum number of shocks was 6. Median cumulative energy was 150 Joules (interquartile range = 387.5 Joules) with the minimum being 50 Joules and maximum being 1730 Joules. A total of 49 (40.8%) patients received a cumulative defibrillation energy of 300 Joules or higher. The highest energy delivered per shock was 360 Joules and median peak impedance levels was 80.80 Ohms (interquartile range = 19.05 Ohms). Median Hs-trop T levels pre-cardioversion was 7 ng/L (interquartile range = 7) and post-cardioversion was 7 ng/L (interquartile range = 6). A Wilcoxon signed-rank test showed no significant difference between pre-and-post cardioversion Hs-Trop T levels (Z = -0.940, p = 0.347). Conclusions: External DC cardioversion did not result in myocardial injury as measured by high sensitive troponin T. The implications of this study is important as patients who are cardioverted and are found to have a significant troponin rise post-cardioversion should be assessed for causes of myocardial injury and not assumed to have myocardial injury due to the cardioversion itself.